A Feasibilty study on the digital transfer switch - Bo-ot, Jose Juan Miguel R. (College of Engineering, 2001)
The Digital Transfer Switch (DTS) is a project conceptualized by I-Gate Solutions and Technologies Corporation. Before pushing through with its production, a feasibility study was conducted to determine the appropriateness and potential of manufacturing the product. The production areas of the product that were studied are the market, technical, organizational, social profitability, and the financial aspects, respectively. Based on the results of the market study, the DTS indeed has potential market in the telecommunications industry, pharmaceutical companies, and also semiconductor manufacturers and hospitals. The technical feasibility was then able to establish the viability of producing the DTS with a standard set of processes, raw materials, and equipment. Given the expected demand in the market study, a production and capacity plan was also formulated. The organization and management study was aimed at determining the appropriate organizational structure and form of ownership for the company. In order to function most efficiently, the DTS was separated into an Individual Business Unit from the parent company I-Gate Solutions and Technologies Corporation. The social profitability study established the benefits to the environment, country and the society of producing the DTS. Finally, the financially study was able to prove that the production of the DTS is very profitable. Based on all the results obtained and the analysis of these data, the production of the Digital Transfer Switch was determined feasible.